Fat free mass index as parameter for nutritional status in non-dialysis chronic kidney disease patients stage 3, 4 and 5 (Medical Journal of Indonesia, 2008)
The aim of this study is to obtain body composition parameters for early detection of PEM in non dialysis CKD (ND-CKD) patients. The study was carried out using the cross sectional design. The subjects of the study consist of 45 ND-CKD patients and 45 healthy subjects matched for age, gender, height and body mass index (BMI). The nutritional status of patients and healthy subjects were classified based on BMI (WHO, 1995) into low, normal and high nutritional status groups. Fat free mass (FFM), FFM-index (FFM-I) and percentage of fat mass (FM percentage) in patients measured by anthropometric technique showed no significant difference with healthy subjects. Using the BIA method, FFM and FFM-I were significantly lower in the ND-CKD patients compared to the healthy subjects (p < 0,05). Significant difference in FFM, FFM-I, FM and FM percentage was observed between the patients with different nutritional status. (p < 0,001). Trend analysis statistical test showed that there is linear correlation of FFM, FFM-I and FM with nutritional status classification. FFM, FFM-I, FM and FM percentage in ND-CKD patients were not significantly different between the three stages of CKD. There was an acceptable degree of agreement between BMI with FFM-I for nutritional assessment in ND-CKD patients. The Receiver Operating Curve test showed the cut off points of FFM-I 14.23 kg/m2 to differentiate undernutrition and normal nutritional status in ND-CKD patients. This study showed FFM-I has good correlation with BMI and can be used to differentiate degrees of nutritional status in stage 3, 4 and 5 ND-CKD patients. FFM-I considered predictor parameters for nutritional status screening in ND-CKD patients. (Med J Indones 2008; 17: 240-7)Keywords: Non dialysis chronic kidney disease, protein energy malnutrition, body composition, fat free mass, fat free mass index